Young Criminologists in the Teaching Practice: Plight and Aspirations - Pioquinto, Paulino; Cuizon, Reynaldo; Amparado, Mauro Allan (JPAIR Multidisciplinary Research, 2019)
This phenomenological study ascertained the plight and aspirations of young criminologists who were engaged in teaching practice. Two research questions were answered: (1) What is the plight of young criminologists in the teaching practice; and (2) What are the aspirations of young criminologists in the teaching practice? It involved ten research informants presently employed with higher education institutions (HEIs) within Central Visayas, Philippines. The collection of information techniques used were in-depth interviews and focus group discussion. The research participants shared their plight in the teaching practice and their aspirations in their career. Nine themes surfaced in this study: low confidence, difficulties in oral and written communication, a teacher by accident, lack of preparation for teaching practice, job satisfaction, professional status, technical skills, professional & personal growth, and support to enhance teaching competence.
Keywords: Criminologists; Teaching Practice; Teaching Competence; Plight; Aspirations; Philippines